Development Of Liveworksheets Based Learning Materials in Class V Sciences Learning of Sukarejo State Elementary School - Yusnita, Nuke Safria; Sahudra, Tengku Muhammad; Mulyahati, Bunga (ALACRITY : Journal of Education, 2025)
The research aims to develop a product of teaching materials based on Liveworksheets for learning science, particularly social studies materials for grade V elementary school students. This study was conducted to evaluate the validity of the teaching materials through validation assessments from material experts, language experts, and teaching material experts, as well as to assess their practicality. The study uses the Research and Development (R&D) approach, employing the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The data collection methods include observation, interviews, documentation, and validation questionnaires for experts, along with response questionnaires for teachers and students. The validation results from material experts showed a percentage of 88% in the "very valid" category, while language experts achieved 90% in the "very valid" category, and teaching material experts scored 80% in the "valid" category. Based on feedback from practitioners through the teacher and student response questionnaires, teacher responses received 89% in the "very practical" category, while student responses reached 93.46% in the "very practical" category. Based on the assessment results of the Liveworksheets-based teaching materials, it can be concluded that these materials are highly suitable for use in grade V science education. For future researchers, it is advisable to conduct field trials to measure the effectiveness of the teaching materials and to develop Liveworksheets-based teaching materials for various subjects in elementary schools.